(untitled) (Fiep Bulletin - online, 2012)
In the seventies, eighties, the portuguese philosopher Manuel Sergio brought up brainstormings inpeople, used to seeing the Man the Cartesian way, split in two - body and spirit, when proposing a new science,the Human Kinetics. Throughout the years, and despite all his prophetic efforts in spreading the news, it seemsthat these dualistc habits basically remain, or maybe, what may have been changed was only in the semanticsfield: Human Kinetics is seen as the most sophisticated name of Physical Education and Sport. In this article, wedenounce this and alert to the danger of facing the multidimensional nature of human being, not only in theontological level, but also in the mere plan of the logical relations. How can we still alert to the danger of a driftcrusader of social transformation, forgetting that any change will only be effective if it takes place in each person’shearts first?